2013
DOI: 10.1111/mec.12317
|View full text |Cite
|
Sign up to set email alerts
|

Influence of late Quaternary climate change on present patterns of genetic variation in valley oak, Quercus lobata Née

Abstract: Phylogeography and ecological niche models (ENMs) suggest that late Quaternary glacial cycles have played a prominent role in shaping present population genetic structure and diversity, but have not applied quantitative methods to dissect the relative contribution of past and present climate vs. other forces. We integrate multilocus phylogeography, climate-based ENMs and multivariate statistical approaches to infer the effects of late Quaternary climate change on contemporary genetic variation of valley oak (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
154
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(177 citation statements)
references
References 104 publications
(111 reference statements)
13
154
3
7
Order By: Relevance
“…The influence of Quaternary climate change on present patterns of genetic variation of some species has been studied [5,6]. Gugger [7] verified that late Quaternary glacial cycles played an important role in shaping the genetic structure and diversity of the present population of Quercus lobata Nee. The results showed that Quercus lobata maintained a stable distribution with local migration from the last interglacial period (~120 ka) through the Last Glacial Maximum (~21 ka, LGM) to the present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of Quaternary climate change on present patterns of genetic variation of some species has been studied [5,6]. Gugger [7] verified that late Quaternary glacial cycles played an important role in shaping the genetic structure and diversity of the present population of Quercus lobata Nee. The results showed that Quercus lobata maintained a stable distribution with local migration from the last interglacial period (~120 ka) through the Last Glacial Maximum (~21 ka, LGM) to the present.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that Quercus lobata maintained a stable distribution with local migration from the last interglacial period (~120 ka) through the Last Glacial Maximum (~21 ka, LGM) to the present. This contrasts with large-scale range shifts in Quercus alba L [7]. More recent climatic oscillations have had profound effects on the dynamics of population expansion and contraction, causing populations to contract into glacial refugia, become extinct and possibly to adapt locally [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary historical processes that infl uence genetic structure is climate change, in particular glacial cycles, which have caused cyclic expansions and contractions of many species' ranges ( Hewitt, 2000( Hewitt, , 2004Tollefsrud et al, 2008 ;Gugger et al, 2013 ;Roberts and Hamann, 2015 ). Phylogeography ( Avise et al, 1987 ) is oft en used to understand the eff ects of glacial cycles on current genetic structure, including the number and location of glacial refugia as well as the recolonization routes from those refugia to current locations ( Hewitt, 1996 ;Taberlet et al, 1998 ;Hewitt, 2000 ).…”
mentioning
confidence: 99%
“…Quercus ), but they differ markedly in recent evolutionary history. The European oaks experienced severe bottlenecks during Pleistocene glaciations, with most populations surviving in southern refugia (Petit et al 2003; Petit et al 2002), while the California endemic oaks have not experienced serious bottlenecks in at least 150,000 yr or more, with evidence of relatively stable species distributions during the last few interglacial cycles (Gugger et al 2013). Many oak studies have utilized genomic approaches, but without the benefit of a reference genome ( e.g.…”
mentioning
confidence: 99%